B cells expressing CD11b effectively inhibit CD4+ T‐cell responses and ameliorate experimental autoimmune hepatitis in mice. Issue 5 (28th September 2015) - Liu, Xiaoming; Jiang, Xuechao; Liu, Ronghua; Wang, Luman; Qian, Tingting; Zheng, Yijie; Deng, Yuting; Huang, Enyu; Xu, Fengkai; Wang, Ji‐Yang; Chu, Yiwei
<x xml:space="preserve">Abstract</x> Increasing evidence in recent years has suggested that B cells act as a crucial regulator in autoimmune diseases. However, little is known about their role in autoimmune hepatitis (AIH) and the underlying regulatory mechanisms. In this study, we show that B cells ameliorated experimental AIH (EAH) by suppressing CD4+ T‐cell responses and that CD11b expression on B cells was required for the regulatory function of B cells. In vitro studies reveal that the suppressive function of CD11b was mediated by the impairment of T‐cell antigen receptor (TCR) signaling transduction and the promotion of TCR down‐regulation. Moreover, we show that the increased CD11b expression on B cells was interleukin (IL)−10 dependent and that additional IL‐10 stimulation promoted CD11b expression on B cells, thereby enhancing B‐cell regulatory effects. Conclusion: These findings reveal a previously unrecognized role for CD11b in B‐cell regulatory function and its protective effect on EAH. (Hepatology 2015;62:1563–1575)